In Vivo Pulse Wave Measurement Through a Multimode Fiber Diffuse Speckle Analysis System - Teng, Zhongshuai; Gao, Feng; Xia, Hua; Chen, Wenliang; Li, Chenxi (Frontiers in Physics, 2021)
Continuous monitoring of in vivo pulsatile blood flow and pulse wave velocity (PWV) is important for clinical applications. These parameters are correlated with physiological parameters, such as blood pressure and elasticity of blood vessels. A multimode fiber diffuse speckle contrast analysis (MMF-DSCA) system was developed for fast measurement of in vivo pulsatile blood flow and pulse wave velocity. With MMF and CCD sensor, the diffuse speckle could be captured and processed with higher temporal resolution of 3 ms. We also induced for the first time an MMF-DSCA for evaluation of PWV, which allows estimation of the blood pressure continuously. To validate its performance, both phantom and in vivo experiments were conducted. The results demonstrate that MMF-DSCA could achieve fast pulsatile blood flow measurement with detailed information of the pulse wave profile and velocity. Taking the advantages of being simple and cost-effective, the flexible system can be easily adapted for continuous monitoring of vital biosigns, such as heart rate, pulse wave, and blood pressure.